KETERSEDIAAN NITROGEN DAN POPULASI BAKERI TANAH DALAM SISTEM TANAM SRI (SYSTEM OF RICE INTENSIFICATION) - Nurul Istiqomah; Tanya Naomi Indarto; Virgus Amien Nugroho; Cahyo Prayogo (BUANA SAINS, 2018)
The obstacles that caused the declining of rice production is due to the reduction of soil fertility status. Various efforts were made to increase the production such as intensification and expansion in rice farming system. SRI cropping systems an alternative technique for improving soil productivity following maintaining water uses under an aerobic condition which exaggerated the raising of microorganisms activities in soil and improving the availability of nutrients particularly nitrogen status.This study was aimed to examine the impact of SRI system on mineral N status along with the population of soil bacteria which involving in nitrogen dynamic. The research was conducted in October 2015-March 2016 in Kepanjen-Malang using Randomized Block Design with 4 treatments and 4 replicates. Soil sampling was conducted at 0 and 100 Day After Planting (DAP) collecting at a depth of 0-20 cm and 20-40 cm. Measured soil parameter was including pH, organic-C, mineral N (NH4+ and NO3-). Soil bacteria are identified using plate count method (spread plate) for estimating their population. Analysis of Variance (ANOVA) was used followed by Duncan test at 5% level along with correlation and regression analysis.The results showed that the SRI cultivation system can increase the mineral N at the level of 14.09 ppm compared to their initial value, amounting to 57.48 ppm of Nitrate and the bacterial population at the level of 6.25 x 108 cfu g-1. The best treatment was found under the combination of NPK (15-15-15) and biofertilizer yielded at 8.42 t ha-1. Multivariate analysis results indicate that P0 treatment significantly different with treatment P1, P2, and P3. However, the treatment of P1 were not significantly different P3.